Optimization of Cast-Steel Tubular Circular-Hollow-Section Connections Based on Depth-First Search Algorithm - Kaien Jiang; Ziming Yang; Ju Chen; Guoer Lv; Huafeng Yu (Buildings)
This study introduces a novel design for a cast-steel joint in the shape of a T, aimed at resolving concerns regarding stress concentration at points where geometric intersections occur and enhancing the quality of welding in T-shaped welded joints. The proposed integrated design framework greatly facilitated the successful construction of a three-dimensional joint between a brace and a chord at a T-shaped node. The geometric parameters of curves in the connector were optimized using a depth-first search algorithm, resulting in control points for the optimized curve. Computer-aided design software was then employed to obtain the refined connector. The design framework has the ability to produce designs with smooth and uninterrupted boundaries, making them highly compatible with traditional casting methods and effectively tackling the manufacturing challenges related to topology optimization. The numerical simulation results demonstrate that, in comparison to traditionally welded T-joints of the same size, the stress concentration factor of the optimized joints exhibits a significant reduction, accompanied by a notable disparity in stress distribution. Moreover, the impact of the thickness of the brace and the axial compression ratio on the stress concentration factor of the optimized joints was relatively insignificant. The stress concentration factor of the cast-steel joint was reduced by more than 84%, leading to a significant enhancement in fatigue performance.